Interferon regulatory factor 3 protects against adverse neo-intima formation. (4th March 2014) - Zhang, Shu-Min; Zhu, Li-Hua; Li, Zuo-Zhi; Wang, Pi-Xiao; Chen, Hou-Zao; Guan, Hong-Jing; Jiang, Ding-Sheng; Chen, Ke; Zhang, Xiao-Fei; Tian, Song; Yang, Da; Zhang, Xiao-Dong; et al.
Abstract: Aims: Vascular smooth muscle cell (VSMC) proliferation is central to the pathophysiology of neo-intima formation. Interferon regulatory factor 3 (IRF3) inhibits the growth of cancer cells and fibroblasts. However, the role of IRF3 in vascular neo-intima formation is unknown. We evaluated the protective role of IRF3 against neo-intima formation in mice and the underlying mechanisms. Methods and results: IRF3 expression was down-regulated in VSMCs after carotid wire injury in vivo, and in SMCs after platelet-derived growth factor (PDGF)-BB challenge in vitro . Global knockout of IRF3 (IRF3-KO) led to accelerated neo-intima formation and proliferation of VSMCs, whereas the opposite was seen in SMC-specific IRF3 transgenic mice. Mechanistically, we identified IRF3 as a novel regulator of peroxisome proliferator-activated receptor γ (PPARγ), a negative regulator of SMC proliferation after vascular injury. Binding of IRF3 to the AB domain of PPARγ in the nucleus of SMCs facilitated PPARγ transactivation, resulting in decreased proliferation cell nuclear antigen expression and suppressed proliferation. Overexpression of wild-type, but not truncated, IRF3 with a mutated IRF association domain (IAD) retained the ability to exert anti-proliferative effect. Conclusions: IRF3 inhibits VSMC proliferation and neo-intima formation after vascular injury through PPARγ activation.